Friedrich List - Wegbereiter eines europäischen Verkehrssystems. Vor 175 Jahren erschien in Leipzig die weltweit erste Verkehrszeitung. - Haase, Ralf (Deutscher Verkehrs-Verl., 2009)
Aus Anlass des 170. Jahrestages der ersten deutschen Ferneisenbahn zwischen Leipzig und Dresden am 7. April 1839 hat sich Heft 6/2009 der Zeitschrift bereits recht umfangreich mit dem engagierten Wirken Lists für dieses Projekt beschäftigt. Ohne seine fachlichen Argumente und seine unermüdliche Überzeugungsarbeit wäre der Bau dieser Bahn zu jenem Zeitpunkt nicht zustande gekommen wäre. Damit hätte es auch keine Initialzündung für den deutschen Eisenbahnbau gegeben und die industrielle Revolution wäre in ihren Wirkungen in den deutschen Teilstaaten auf Jahre oder Jahrzehnte verzögert worden. Um diese Feststellung verstehen zu können, muss man Lists Biografie kennen. Einige markante Bezüge sollen dies verdeutlichen.

The life and achievements of Friedrich List (1789-1846) are closely associated with the political and economic changes at the beginning of the nineteenth century, which involved the phasing out of the aristocracy-controlled feudal system of governance and the evolution of an economy structured along the principles of capitalism, both in Germany and across Europe. As a democrat involved with the struggle over a new constitution, as a theorist concerned with economy-related issues, as a force behind the efforts aimed at countering the fragmentation of Germany's economy, and as a pioneer helping to create a modern transport system based on the railways, List - for being a leading proponent of a range of issues - was confronted with society's hostile attitudes throughout his life. His enduring achievements include his work aimed at the creation of a unified national economy, the planning and construction of a rail network, and devising concepts for modern economy- and transport- related theories. List thus belonged to the group of eminent political economists who sought to guide theories towards purposeful policies for the economy, commerce and transport. Because of his efforts aimed at formulating basic theories for the transport system, list deserves the honour of having been instrumental in founding "transportation science" across the world.
Friedrich List - the spiritual power behind a modern European system of transport.
Keywords: Landesgeschichte; Verkehrswirtschaft; Schienenverkehr; Verkehrssystem; Wirtschaftstheorie; Eisenbahn; Infrastruktur; Verkehrsinfrastruktur; Zoll; Geschichte; Presse; Biographie; Wirtschaftsgeschichte; Maut; Europa; Eisenbahngeschichte; Zeitung